Fatwa and the Question of Meaning: A Hermeneutic Reading of Zakat on Illicit Wealth - Muhammad Fauzinudin Faiz; Aouich, Abdelmalek; Miftahussur, Wildan (UIN Sunan Kalijaga, 2025)
Illicit wealth is legally excluded from the obligation of zakat; however, it remains morally conceptualized as requiring purification. This article examines the interpretation of zakat on illicit wealth through a hermeneutic analysis of Fatwa No. 13 of 2011, issued by the Indonesian Ulama Council (Majelis Ulama Indonesia, MUI). The fatwa asserts that zakat is not obligatory on unlawfully acquired assets, as such wealth is not legally recognized under Islamic law. Rather than concentrating on the doctrinal legitimacy of this stance, the study investigates how religious communities comprehend and respond to the fatwa in relation to moral purification and wealth redistribution. Employing Hans-Georg Gadamer’s notions of pre-understanding (Vorverständnis) and fusion of horizons (Horizontverschmelzung), the research utilizes a philosophical hermeneutic approach within a socio-legal framework. It conceptualizes the fatwa not merely as a static legal document but as an interpretive event situated within a dynamic dialogue between normative teachings and lived social meanings. The findings reveal that many Muslims regard zakat not only as a legal duty but also as a spiritual act of cleansing, even when the wealth originates from unlawful sources. This highlights a disjunction between the legal content of the fatwa and the moral imagination of its public audience. The study concludes that fatwas should not be interpreted as unequivocal commands but as discursive texts negotiated through shared ethical and cultural horizons.